AN ANALYSIS OF PRESUPPOSITION ON BRAD COHEN’S CHARACTER IN FRONT OF THE CLASS MOVIE - Kenedi Wahyu Saputra; M. Bahri Arifin; Setya Ariani (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
The objectives of this research were to describe the types of presupposition used by the main character in Front of the Class movie and identify the meanings of utterances containing presupposition used by main character in Front of the Class movie. Yule‟s theory of presupposition is used by the researcher to answer the formulated research questions. This research was a qualitative study applying descriptive-qualitative method. The subject of this research is a movie entitled Front of the Class directed by Peter Werner. The data were some scenes including the utterances said by speaker and heard by hearer. The data analysis was conducted by identifying and classifying the data to find the inferences. The findings of the research are as follows: in Front of the Class movie, all Yule‟s six types of presupposition are found. Those are; existential presupposition, factive presupposition, non-factive presupposition, lexical presupposition, structural presupposition and counterfactual presupposition. The meanings of utterances containing presupposition used by main character in Front of the Class movie are gained by analyzing the context because in pragmatic study, context is essential to figure out the implied meaning. The context of the Brad Cohen's utterances in Front of the Class movie is gained through three factors. They are; the participants, the context of situation and the shared knowledge.